Centellograma tiroideo - Artagaveytía, Daniel; Pecorini, Victorio; Gotta, Héctor; Degrossi, Osvaldo Jorge (Comisión Nacional de Energía Atómica (CNEA), 1964)
Fil:Artagaveytía, Daniel Comisión Nacional de Energía Atómica (CNEA). República Argentina